Potensi Manusia Dalam Perspektif Al-Quran - Aini Qolbiyah; Munzir Hitami; Kadar M. Yusuf (Yayasan Literasi Kita Indonesia, 2022)
Human self-potential is a basic ability possessed by humans that is still hidden inside them waiting to be realized into a real benefit in human life. This research was designed in the form of a library research or Library research that uses various sources of literature as a data source that relates to the thinking of a character who at a certain time, cultural conditions, the community at that time, along with documents, then the methodologically used approach is interpretation. The results showed that human potential consists of the potential of the senses, qalb / heart aql/ ,?????fu'ad/ ??????and .?????/'dz